Clear, crashing, turbid and back – long‐term changes in macrophyte assemblages in a shallow lake. (20th June 2013) - Hilt, Sabine; Köhler, Jan; Adrian, Rita; Monaghan, Michael T.; Sayer, Carl D.
Summary: During eutrophication, submerged macrophytes in temperate European shallow lakes are thought to undergo a sequence from seasonally 'stable' conditions characterised by high water clarity in spring and summer, through 'crashing' conditions where the water is clear in spring but dominated by phytoplankton in late summer, to 'turbid' conditions with year‐round phytoplankton dominance. However, it is not known whether this sequence is reversed during re‐oligotrophication and whether this contributes to the often observed delay in macrophyte recovery during lake restoration. We analysed long‐term (100 years) data on macrophyte species presence, maximum colonisation depth, Secchi depth and seston concentration in shallow Lake Müggelsee during eutrophication from around 1900 and during re‐oligotrophication that started in 1990. The current clonal diversity of the dominant species ( Potamogeton pectinatus ) was investigated to determine whether vegetative dispersal was predominant during its re‐establishment. During eutrophication, Lake Müggelsee went through a crashing phase for c . 70 years with a gradual decline in macrophyte species diversity from c . 24 to 5 species. From around 1970, the lake became turbid and was dominated by phytoplankton for the next 20 years. Following a reduction in external nutrient loading by 50% from 1990, spring clear‐water conditions immediately re‐appeared, and P. pectinatus started to re‐establish from a few stands that had survived in very shallow areas. By 2011, species diversity had increased to 25 species and maximum colonisation depth had reached 3.2 m. Despite a continuing dominance of P. pectinatus, seasonally persistent ( Ceratophyllum demersum ) and late‐season associated ( Najas marina ) species re‐appeared suggesting potential for seasonally stable macrophyte conditions in future. Based on microsatellite analyses, more recently established P. pectinatus stands had lower genotype diversity and were comprised of only a small subset of genotypes from shallower areas, suggesting that vegetative dispersal was more important than seed dispersal for plant re‐establishment. We argue that this prevailing reproduction by tubers in combination with negative effects of herbivory and periphyton shading, shown for P. pectinatus in earlier studies in this lake, contributed to the long duration of macrophyte re‐establishment.